1992
DOI: 10.1136/bjo.76.9.538
|View full text |Cite
|
Sign up to set email alerts
|

Tono-Pen tonometry in normal and in post-keratoplasty eyes.

Abstract: Oculab Tono-Pen tonometry was compared with Goldmann applanation tonometry in 82 eyes of 82 patients with normal corneas and in 54 eyes of 54 patients who had undergone penetrating keratoplasty and whose corneas did not preclude the use of the Goldmann tonometer. We found that the intraocular pressure (IOP) This instrument has certain advantages over the Goldmann applanation tonometer. It is portable and compact, can be used regardless of the patient position, is easy to calibrate and operate, has a disposal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 4 publications
3
19
1
1
Order By: Relevance
“…When the Tono-pen was compared with the MacKay-Marg tonometer, there was no significant difference in IOP measurement in normal corneas and in corneas after PKP and epikeratophakia [87]. However, Geyer et al found the Tono-pen to overestimate compared with the Goldmann tonometry readings in both normal and post-keratoplasty eyes, especially in the lower IOP range (\9 mmHg) [88]. Another electronic portable tonometer similar to the Tono-pen is the ProTon tonometer.…”
Section: Tonometrymentioning
confidence: 96%
“…When the Tono-pen was compared with the MacKay-Marg tonometer, there was no significant difference in IOP measurement in normal corneas and in corneas after PKP and epikeratophakia [87]. However, Geyer et al found the Tono-pen to overestimate compared with the Goldmann tonometry readings in both normal and post-keratoplasty eyes, especially in the lower IOP range (\9 mmHg) [88]. Another electronic portable tonometer similar to the Tono-pen is the ProTon tonometer.…”
Section: Tonometrymentioning
confidence: 96%
“…Several authors have demonstrated that the TonoPen XL tends to overestimate low IOPs and underestimate high IOPs [12][13][14], while others have concluded that there is no such variation [15,16].…”
Section: Discussionmentioning
confidence: 96%
“…Literatürde farkl› ölçüm yöntemlerini karfl›laflt›ran birçok çal›flma mevcuttur. Bu öl-çüm yöntemlerinden tonopen ve GAT ile ölçümler aras›n-da uyum oldu¤unu bildiren çal›flmalar (12)(13)(14)(15) (16)(17)(18)(19)(20). Bir çal›flmada tonopen ve GAT ile elde edilen ölçümler aras›nda 20 mmHg'nin alt› için iyi bir uyum oldu¤u ancak 20 mmHg'nin üstündeki bas›nçlar için tonopenin anlaml› olarak daha düflük ölçüm yapma e¤ilimi gösterdi¤i bildirilmifl ve tonopenin güveni-lirli¤inin GAT ile karfl›laflt›r›labilir oldu¤u savunulmufltur (12).…”
Section: Tart›flmaunclassified